Light-specific transcriptional regulation of the accumulation of carotenoids and phenolic compounds in rice leaves. (2nd June 2016) - Mohanty, Bijayalaxmi; Lakshmanan, Meiyappan; Lim, Sun-Hyung; Kim, Jae Kwang; Ha, Sun-Hwa; Lee, Dong-Yup
ABSTRACT: Carotenoids and phenolic compounds are important subgroups of secondary metabolites having an array of functional roles in the growth and development of plants. They are also major sources for health and pharmaceutical benefits, and industrially relevant biochemicals. The control of the biosynthesis of these compounds depends mainly on the quality and quantity of different light sources. Thus, to unravel their light-specific transcriptional regulation in rice leaves, we performed promoter analysis of genes upregulated in response to blue and red lights. The analysis results suggested a crosstalk between different phytohormones and the involvement of key transcription factors such as bHLH, bZIP, MYB, WRKY, ZnF and ERF [jasmonic acid inducible], in the regulation of higher accumulation of carotenoids and phenolic compounds upon blue light. Overall, the current analysis could improve our understanding of the light-specific regulatory mechanism involved in the biosynthesis of secondary metabolites via possible critical links between different TFs in rice leaves.